Tiger time 6 : student's book with eBook - Read, Carol (London : Macmillan Education, 2015)
Within each unit of the Student's Book are lessons that have been structured to focus on vocabulary, grammar and skills, and then building to CLIL, culture and projects. A code gives access to the Student's Resource Centre where a digital platform offers a wealth of extra material. Also included is an eBook version of the Student's Book.
Keywords: English language -- Study and teaching (Elementary) -- Foreign speakers; English language -- Study and teaching (Elementary)